2018
DOI: 10.1007/s10811-018-1650-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant content and activity of the seaweed Saccharina latissima: a seasonal perspective

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 52 publications
9
30
2
1
Order By: Relevance
“…This might indicate that HPP does not influence the seaweed extract TPC. In general, it should be noted that the TPC of all of these seaweed extracts was quite low, in line with the literature [22,40,41]. A high variability in the TPC of seaweeds, in particular that of H. elongata, has been previously reported, due to multiple factors such as collection season and geographical region [9,40].…”
Section: Total Phenolic Contentsupporting
confidence: 86%
“…This might indicate that HPP does not influence the seaweed extract TPC. In general, it should be noted that the TPC of all of these seaweed extracts was quite low, in line with the literature [22,40,41]. A high variability in the TPC of seaweeds, in particular that of H. elongata, has been previously reported, due to multiple factors such as collection season and geographical region [9,40].…”
Section: Total Phenolic Contentsupporting
confidence: 86%
“…The consumption of seaweed as an antioxidant rich food increased due to their protective effects against reactive oxygen species (ROS) which induced oxidative damage in human cells leading to various chronic diseases. The presence of natural antioxidants such as phenolics and flavonoids that bear hydroxyls functional groups in seaweed, which, among other nutritional properties, makes it an important functional food to inhibit oxidative stress donating hydrogen to stabilize and prevent the generation of free radicals [ 7 , 16 , 65 ], enabling it to reduce disease risk and health promotion [ 66 ]. The TPC and TFC content in the analysed seaweed samples were quantified as 17.88 ± 0.78 mg GAE g −1 and 59.43 ± 2.45 mg QE g −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Abiotic factors such as levels of irradiance levels, temperature, nutrient availability, precipitation, salinity [ 47 ] and biotic factors such as grazing pressure, reproductive state and stage of life cycle affect polyphenols content in seaweed. As the seaweed analysed were collected from earthen fish ponds which is high in nutrients, this factor could contribute to levels of phenolic and flavonoid in the seaweed, affecting its antioxidant capacity [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has to be taken into account that the concentration of phenols may present a wide range of variability in these kind of matrices. It was indeed demonstrated that total phenolic amount was strongly influenced by several factors such as seasonality, temperature, light intensity, and water salinity [ 78 ]. This may explain why H. elongata extracts I and II showed a significant different phenolic content ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%